Variation in age composition among colony sizes in Cliff Swallows. Issue 3 (26th August 2014) - Brown, Charles R.; Roche, Erin A.; Bomberger Brown, Mary
ABSTRACT Variation in group size is characteristic of most social species. The extent to which individuals sort among group sizes based on age may yield insight into why groups vary in size and the age‐specific costs and benefits of different social environments. We investigated the age composition of Cliff Swallow (Petrochelidon pyrrhonota) colonies of different sizes over 18 yr at a long‐term study site in western Nebraska, USA. Using years elapsed since banding as a relative measure of age for over 194, 000 birds, we found that the proportion of age‐class‐1 swallows (birds banded as nestlings or juveniles or adults in the year of banding) of both sexes increased in larger colonies and at colony sites becoming active later in the summer. Age composition was unrelated to how often a particular colony site was used. The effect of colony size most likely reflected the fact that older birds return to the same colony site in successive years even when the colony size there decreases, and that yearlings and immigrants benefit more from larger colonies than do older, more experienced individuals. The date effect probably resulted in part from later spring arrival by younger and/or immigrant swallows. At fumigated sites where ectoparasitic swallow bugs (Oeciacus vicarius) had been removed, age composition did not vary with either colony size or colony initiation date. The patterns reported here appear to be driven partially by the presence of ectoparasites and suggest that the hematophagous bugs influence variation in Cliff Swallow group composition. Our results are consistent with the hypothesis that variation in colony size reflects, in part, age‐based sorting of individuals among groups.